The dynamics of jama (jamu madura-madurese traditional herbal medicine) in the viewpoint of public woman: a phenomenology study - Sri Yunita Suraida Salat; Ahmaniyah Ahmaniyah; Emdat Suprayitno (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2021)
Background: With the progress and development of medicine that is currently happening, there are still many people in Sumenep who choose Madurese traditional herbal medicine in an effort to prevent and to cure disease, in the process of pregnancy, childbirth and the postpartum period. This habit was inherited from their ancestors. Jamu is supposed to provide benefits and safe with no side effects. People in Sumenep still consuming herbal medicine during postpartum period as habit. Objectives: This study aimed to describe views and opinions of postpartum mothers on the puerperal herbal medicine that they consumed during the postpartum period. Methods: This study exploring the local culture, postpartum mothers’ knowledge about postpartum herbal medicine and their perception about its benefits. This study design was qualitative study with a phenomenological approach with total participants were 20 postpartum mothers and their families and 2 postpartum herbal medicine makers. Data were collected by direct observation through in-depth interviews. Results: The results showed 5 themes describing the dynamics of the Madurese traditional herbal medicine in the viewpoint of post-partum mothers, namely their reasons for consuming postpartum traditional herbal medicine, the form of the herbal traditional medicine consumed, their knowledge of postpartum herbal medicine, the benefits of postpartum traditional herbal medicine, and the mother's desire to consume the puerperal herbal medicine in the future. Conclusions: It can be concluded that there was different viewpoint that described by postpartum women about consuming postpartum herbal medicine. In general, they found that postpartum herbal medicine had benefits directly in the recovery process of the postpartum period and increasing breast milk production.